College students perceptions of the use of mobile devices during lessons - Schnitman , Ivana Maria (Seven Editora, 2023)
One of the cultural signs of contemporaneity is the intense relationship between youth and their mobile devices. In this context, mobile technologies, especially, notebooks and smartphones are used not just as a communication artifact, but as a space to mediate the face-to-face and virtual realities. This article intends to investigate the role those devices, considering their different uses have on college students' learning experience within the classroom. The research examines in what sense student’s behavior is changing by analyzing the relationship between different uses of mobile devices and students' learning habits inside the classroom. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-077